Kontribusi Indo Europeesch Verbond (IEV) pada Penguatan Identitas Keeropaan dan Solidaritas Indo - Praheningtyo, Raden Welling; Amini, Mutiah (Department of History, Faculty of Humanities, Diponegoro University, 2024)
This study focuses on the strengthening of identity and solidarity among the Indo community through the establishment of the Indo Europeesch Verbond (IEV) during the period of Indonesia's national movement. The aim of this study is to analyze the movements of the IEV in voicing the aspirations of the minority Indo group. Social segregation, both imposed by the Dutch colonial government and practiced socially, also led to an identity crisis for the population of the Dutch East Indies, which consisted of various ethnicities and races. The identity crisis also affected the Indo community, as descendants of mixed European and Dutch East Indies heritage. The identity concept developed by the Indo group was to act as an intermediary between Western and Eastern cultures. Using historical methodology, this study outlines the background of the formation of the IEV and the programs organized to assert the existence of the Indo group. The formation of identity began with collective awareness and the shared sense of discrimination, which then manifested in the desire to form associations and organizations. The research findings show that the IEV implemented various welfare programs to build solidarity, such as education and scholarships, colonization (transmigration), and the movements of Indo women and youth. In addition to welfare programs, political pathways were also pursued, notably through representatives in the Volksraad. This study demonstrates that an organization plays a significant role in the formation of identity and solidarity within the Indo community, which had its own unique characteristics in the context of Indonesia's national movement.